2013
DOI: 10.1039/c2cc37933c
|View full text |Cite
|
Sign up to set email alerts
|

Maximum hydrogen chemisorption on KL zeolite supported Pt clusters

Abstract: Platinum clusters supported on KL zeolites were characterized by EPR, HRTEM, and EXAFS. Two kinds of hydrogen chemisorption experiments both result in a saturation value of 2.9 hydrogen atoms per platinum atom, significantly more than that reported so far. A hydrogen coverage-dependent cluster restructuring is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 16 publications
10
47
0
4
Order By: Relevance
“…3,6 Then the first spectrum is recorded and used as a background for the following difference spectra when the hydrogen pressure is stepped up in increments before measurement of the difference spectra. Hydrogen adsorption and measurement of spectra was conducted at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…3,6 Then the first spectrum is recorded and used as a background for the following difference spectra when the hydrogen pressure is stepped up in increments before measurement of the difference spectra. Hydrogen adsorption and measurement of spectra was conducted at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…4 In contrast to bulk Pt which chemisorbs one hydrogen atom per surface Pt atom the nanoclusters adsorbs up to 3 H per Pt. 3 The adsorption isotherm was shown to saturate at this value already at a hydrogen pressure of ca. 70 mbar at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding is not understood at this point, but it should be reminded that under the given conditions the surface even of a noble metal is not always a blank metal. After reduction in hydrogen it may be covered by chemisorbed hydrogen 38 or if exposed to air it may be contaminated with oxygen species. In particular, it has also been reported that after hydrogen reduction the metal of Ru/TiO 2 and other titania-supported noble metal catalysts are covered to a substantial degree with a titania overlayer and that this affects the turnover number considerably.…”
Section: Interpretation Of Charge Transfer and Its Dependence On The mentioning
confidence: 99%